Characterization of bioflocculant-producing bacteria isolated in Vietnam and its use for harvesting indigenous microalgae - Tu, Le Thi Anh (Academia Journal of Biology, 2018)
Bioflocculation producing bacteria isolated from soil and sediment in Da Lat City, Lam Dong Province, Vietnam, were characterized. Four bacterial strains that had high flocculation activity were Flavobacterium granuli CL, Hydrogenophaga pseudoflava DA, Alcaligenes cupidus PT2, Bacillus mucilaginosus PT3, with the flocculation efficiency of 91.37%, 83.12%, 76.92%, and 75.81%, respectively at 22°C, pH 10, the initial algae concentration (optical density at 690 nm) of 1.25, and grown in media containing glucose as the carbon source. The bioflocculation efficiency was depended on the pH, carbon sources, the initial algae concentrations, bacteria strains, and the inital bioflocculant-producing bacteria concentrations. The temperature lightly affected the bioflocculation, no noticeable behavioral or activity changes were observed in mice that were orally administrated with four bacterial strains, and no treatment-related illness or death occurred after 72 hours. In general, the bioflocculation process is easy to operate, cost-effective, environment-friendly and therefore, it can be applied for industrial processing of microalgae.